2000
DOI: 10.1111/j.0014-3820.2000.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for the Evolution of Soldier Sperm Classes

Abstract: Abstract. There has been wide disagreement as to whether sperm competition among animals can produce a soldier class of sperm to fight against other males. Utilizing mathematical models, we analyze the appropriate conditions for the evolution and maintenance of a soldier sperm class. We conclude that: (1) soldier sperm evolve even if one soldier sperm can kill or block less than one competing sperm; (2) soldier sperm evolve faster when there is a large variance in the number of competing sperm; (3) soldier rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The hypothesis that parasperm are produced to enhance males' success in cryptic female choice predicts the production of larger/more parasperm when postcopulatory sexual selection is more frequent (Holman and Snook 2006), which we did not observe. In contrast, a model of the evolution of hypothetical "soldier sperm" (e.g., displacers or killers of rival eusperm) suggested that selection would minimize the size of each soldier (Kura and Nakashima 2000). The idea that parasperm are displacers has not been experimentally tested in the obscura group, but our results suggest it may be worth pursuing.…”
Section: Dependent Variablementioning
confidence: 61%
“…The hypothesis that parasperm are produced to enhance males' success in cryptic female choice predicts the production of larger/more parasperm when postcopulatory sexual selection is more frequent (Holman and Snook 2006), which we did not observe. In contrast, a model of the evolution of hypothetical "soldier sperm" (e.g., displacers or killers of rival eusperm) suggested that selection would minimize the size of each soldier (Kura and Nakashima 2000). The idea that parasperm are displacers has not been experimentally tested in the obscura group, but our results suggest it may be worth pursuing.…”
Section: Dependent Variablementioning
confidence: 61%
“…As our simple analysis shows (Figure 1), negative relatedness between sperm abounds within the sperm storage organ of a promiscuous female, in which sperm of multiple males mingle, setting the scene for spite. The idea that sperm harm one another dates back 25 years in the empirical literature [2629]. But is this really spite?…”
Section: Spitementioning
confidence: 99%
“…Males that invest some of their resources in parasperm may consequentially have more eusperm available for sperm competition and/or have an increased likelihood of fertilisation in matings with females that only mate once. The evolution of parasperm for 'sacrificial' functions has been modelled before, but this work models a situation where parasperm attack the sperm of rival males ('kamikaze sperm'; Kura & Nakashima, 2000). Our model also differs from the Kura & Nakashima (2000) model in that rather than simply demonstrating that Yes, as parasperm number/quality is predicted to be an important determinant of male reproductive success Offence Defence parasperm could evolve, we also estimate how much should be invested in parasperm.…”
Section: The Sacrificial Sperm Hypothesis For the Evolution Of Paraspermmentioning
confidence: 99%
“…The evolution of parasperm for 'sacrificial' functions has been modelled before, but this work models a situation where parasperm attack the sperm of rival males ('kamikaze sperm'; Kura & Nakashima, 2000). Our model also differs from the Kura & Nakashima (2000) model in that rather than simply demonstrating that Yes, as parasperm number/quality is predicted to be an important determinant of male reproductive success Offence Defence parasperm could evolve, we also estimate how much should be invested in parasperm. Another model on the evolution of sperm number in response to female spermicide (Greeff & Parker, 2000) only considers changes in sperm-monomorphic ejaculates.…”
Section: The Sacrificial Sperm Hypothesis For the Evolution Of Paraspermmentioning
confidence: 99%
See 1 more Smart Citation